Determinates of Demand on Purchasing Insurance Policies: Case of Jordan - Al-Rawashdeh, Firas (International Review of Management and Marketing, 2017)
This study investigates the determinates of demand on purchasing insurance policies in Jordan to provide empirical evident which would assist insurance companies and policymakers by using these findings to design future insurance services and policies that can be geared to promote insurance market development. The study sample consists of (331) individual and (331) institutions. Total distributed questionnaires were (662), and total of (552) valid questionnaires were returned and included in the analysis. Descriptive statistics and stepwise logistic regression have been used to investigate whether the variables (Promotion and advertisements, cost, social safety, comparative advantage, quality and income) are able to explain the demand on insurance policies in Jordan. The results show that the variables (Promotion and advertisements, social safety, comparative advantage and quality) have a significant effect on the demand of insurance policies while the variables (Cost and Income) were statistically insignificant and have no effect on the demand. Based on the findings it is recommended that the insurance companies should promote their insurance services through advertisement campaigns, and innovate their services in order to compete effectively, gain competitive advantage, and increase the service quality. Keywords: Insurance companies, Demand, Cost, Quality JEL Classifications: G220, L840, L150